KAJIAN AWAL PERSEPSI PENGEMUDI KENDARAAN PENUMPANG TERHADAP KENDARAAN BERAT DI JALAN TOL - IGW Samsi Gunarta (Jurnal Jalan-Jembatan, 2010)
The presence of heavy vehicles in the carriageway can put passenger-vehicle's drivers in tension that cause these drivers tend to get away form the situation as soon as possible. The study is designed to discover factors causing driving-distractions to and type of distractions that are mostly complained by passengger-car drivers when theyhave to share a carriageway with heavy vehicles. Interviews were carried out to 29 passenger-car drivers of 29-46 years old, with a variation in the expressway driving frequency per year, using a close-ended questionnaires. From the answer, it yielded that the most complained distraction experienced by these drivers was the lack of control over the vehicle when they were overtaking or overtaken by heavy vehicle. The distraction reduces sense of safety of passesger - vehicle which is closely related to the age ofthe driver, dimension and speed of heavy vehicle drivers which is closely related to the age of the age of the driver, dimession and speed of heavy vehicles, enission concentration generated by heavy vehicles and experiences the driver driving on the expressways. The study indicates that reduction in sense of safety is a predominant reason for the instability of traffic flow when a dedicated lane for heavy vehicle is not provided in the expressway. Key words : Traffic Safety, Traffic Interaction, heavy vehicle, sense of safety, Overtaking Maneuvers